ANALISIS STRES KERJA DAN MOTIVASI KERJA PENGARUHNYA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA PT. LEADING GARMENT BANDUNG - Lita Wulantika; Irma Irma (JURISMA : Jurnal Riset Bisnis & Manajemen, 2012)
ABSTRACTThe purpose of this study was to determine: (1) Stress the employee on PT.Leading (2) Motivation of employees working on PT.Leading garment industries, (3 ) The productivity of employees on PT.Leading garment, (4) Effect of work stress and work motivation on PT.Leading garment industries partially or simultaneously. The research method the authors used in this research is descriptive research method and research methods verifikatif. Samples from this study and over 120 are employees. To be able to analyze the extent of the influence of job stress and work motivation on work productivity, methods of analysis used simple and multiple linear regression or correlation of multiple determination. From the results of this study indicate that job stress and work motivation proved to significantly affect employee productivity on PT.Leading garment. These results are demonstrated by statistical tests.The amount of the partial effect of job stress variables on the productivity of employees working on PT.Leading Garment of 21.7%. The amount of the partial effect of motivation to work towards the production of employee productivity on garment PT.Leading Industries of 31.4%. While simultaneously work stress and work motivation affects the productivity of employees working part sewing production orders on men's pajama PT.Leading garment industries of 53.1% and the remaining 46% is influenced by factors that are not researched by the author.Keywords : Work Stress, Work Motivation, Work Productivity